Social Phenotypes of Autism Spectrum Disorders and Williams Syndrome: Similarities and Differences - Asada, Kosuke; Itakura, Shoji (Frontiers in Psychology, 2012)
Autism spectrum disorders (ASD) and Williams syndrome (WS) both are neurodevelopmental disorders, each with a unique social phenotypic pattern. This review article aims to define the similarities and differences between the social phenotypes of ASD and WS. We review studies that have examined individuals with WS using diagnostic assessments such as the Autism Diagnostic Observation Schedule (ADOS), cross-syndrome direct comparison studies, and studies that have individually examined either disorder. We conclude that (1) Individuals with these disorders show quite contrasting phenotypes for face processing (i.e., preference to faces and eyes) and sociability (i.e., interest in and motivation to interact with others), and (2) Although the ADOS and a direct comparison study on pragmatic language ability suggest more deficits in ASD, individuals with WS are similarly impaired on social cognition and communicative skills. In light of these results, we discuss how cross-syndrome comparisons between ASD and WS can contribute to developmental theory, cognitive neuroscience, and the development and choice of clinical treatments.